Relationship between anthropometry attributes and cardiovascular fitness among male Universiti Putra Malaysia futsal athletes / Azhar Yaacob … [et al.] - Yaacob, Azhar; Nur Marthuan, Siti Zubaidah; Nurhalim, Shahrulnizar; Norjali Wazir, Mohd Rozilee Wazir (Universiti Teknologi MARA, 2023)
Anthropometry attributes are among the contributing factors needed to ensure the good performance of athletes. Anthropometry attributes can also be used as an indicator for other fitness components. The present study aimed to determine the relationship between anthropometry attributes and cardiovascular fitness among male Universiti Putra Malaysia futsal athletes. A total of 14 male university futsal athletes participated in this study. Anthropometry measurements taken in this study were height, weight, BMI, body fat percentage, and skeletal muscle percentage. For cardiovascular fitness test, several tests were conducted which were the Beep test, Illinois agility test and Running Anaerobic Strength Test (RAST). The correlation test showed that weight, BMI, and body fat percentage have a negative relationship with VO2 max and a positive relationship with the fatigue index. On the other hand, skeletal muscle percentage showed a positive relationship with VO2 max. The results show that anthropometry attributes have a relationship with cardiovascular fitness, especially VO2 max.